Assembling Formal and Informal Urban Governance: Political Brokerage in Recife, Brazil - Koster, Martijn (Anthropologica, 2019)
This article approaches urban governance as an assemblage of formal and informal practices, comprising official procedures and personal favours, of legal frameworks and private arrangements between bureaucrats and residents. Within such assemblages, I show how community leaders of low-income neighbourhoods in the city of Recife, Brazil, operate as brokers between the state and their fellow residents. The community leaders are key actors in forging alignments between the different elements of the assemblage, using both formal (for example, participatory programs) and informal means (for example, clientelist votes-for-favours exchanges). Combining the anthropology of brokerage with recent assemblage-based work from urban studies and development studies, I conceptualise these local leaders as special “assemblers.” I argue that they are a valuable starting point for analysing urban governance as a formal/informal assemblage, an analysis that provides insights that contribute to recent debates on the informal dimensions of urban governance and, more generally, the interconnections between the formal and the informal. A focus on their connective practices contributes to theorising urban governance as a piecing together of different actors, institutions and resources that is productive of power structures that become manifest in concrete formal and informal acts of assembling.